Sequence diversity of the uniparentally transmitted portions of the genome in the resident population of Catalonia. (November 2022) - Font-Porterias, Neus; García-Fernández, Carla; Aizpurua-Iraola, Julen; Comas, David; Torrents, David; de Cid, Rafael; Calafell, Francesc
Abstract: Genomic reference databases of residing populations are available in different countries and regions. Since they represent the whole genetic diversity of a geographical region, they have wide applications, from biomedical studies to forensic identifications. Uniparentally transmitted portions of the genome specifically are highly suitable for kinship analyses, mixed DNA cases and geographical ancestry inferences. We have sampled 808 individuals currently residing in Catalonia within the GCAT cohort, from which we have generated 808 high-quality whole mitochondrial DNA (mtDNA) genomes and 399 sequences of the male-specific part of the Y chromosome (MSY). We observe higher genetic diversity than in classical population genetics datasets. We test the robustness of whole sequences for unequivocal identifications, and we found that they have higher resolution than mitochondrial control region and Y chromosome short tandem repeats (Y-STRs), and that most of the variants they present are at low frequencies, increasing the discrimination capacity between individuals. These results confirm the forensic applicability of whole uniparental sequences and provide one of the largest high-quality reference datasets ever published. Highlights: Sequenced the whole mtDNA in 808 individuals, 8 Mb of Y chromosome in 399. Samples from population residing in Catalonia, regardless of ancestry. Increased informativeness over mtDNA control region or Y-STR haplotypes. Non-European sequences could represent recent or ancient migrations. ∼22% of the individuals carry at least one heteroplasmic site in their mtDNA.